Effect of Lubricant Formulations on the Tribological Performance of Self-Mated Doped DLC Contacts: a review - Zahid, R.; Masjuki, Haji Hassan; Varman, Mahendra; Mufti, R.A.; Kalam, M.A.; Gulzar, M. (Kluwer (now part of Springer), 2015)
Abstract Diamond-like carbon (DLC) coatings have emerged as one of the most promising surface coatings for applications involving boundary lubrication regime. Some of the characteristics that distinguish DLC coatings from other hard coatings include high hardness, low friction coefficient, wear resistance, and chemical inertness. Because of their low surface energies, these coatings cannot react effectively with different lubricant constituents. Doping of DLC coatings with metals and nonmetals, such as titanium, tungsten, silicon, chromium, fluorine, and nitrogen, can improve their interaction with lubricants to form tribologically beneficial films. Many experimental studies have been conducted on different types of DLC coatings using various lubricant formulations in the last few decades. The results obtained from these experimental studies are very scattered and contradictory, so the data should be consolidated in a more organized and apprehensible manner. By doing so, tribological behavior of various DLC-lubricant combinations can be understood in a better way, and a more logical continuation of research on DLC coatings can be carried out. In this review paper, most widely investigated metal- and nonmetal-doped DLC coatings, such as Ti-DLC, W-DLC, Si-DLC, Cr-DLC, WC-DLC, and multilayered a-C:H/W-DLC coatings, are considered for evaluation. Tribological performance of the aforementioned DLC coatings, in combination with various base oils and lubricant additives, is analyzed by comparing their average friction and wear coefficient values, which have been calculated from published experimental data. Only self-mated doped DLC contacts are considered in this study to eradicate the interference of ferrous and nonferrous counterbodies.